Pengembangan Media Pembelajaran Interaktif Berbasis Adobe Flash Cs6 Untuk Meningkatkan Prestasi Belajar Matematika Peserta Didik Kelas IV SD Kasongan Bantul - Silvana, Nela Alya; Hermawan Wahyu Setiadi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to evaluate the feasibility, practicality, and effectiveness of interactive learning media based on Adobe Flash CS6 in improving the learning achievement of fourth grade students. The research method used is Research and Development (R&D) with Thiagarajan's 4D development model, which includes the Define, Design, Development, and Disseminate stages. This research involved 56 fourth grade students of SD Kasongan as research subjects. The research data were collected through observation, interviews, questionnaires, and tests, then analyzed using descriptive qualitative and quantitative analysis. The research shows that the developed media has a very high level of feasibility based on the assessment of media experts (average score 4.4) and material experts (average score 4.38). In addition, the media was rated very practical based on positive responses from students (82%) and teachers (90%). The effectiveness analysis using statistical tests showed significant differences between the control class and the experimental class (Sig. 2-Tailed = 0.001), it was concluded that the developed media was effective in improving student learning achievement in mathematics subjects.